(untitled) (Journal of Educational Sciences, 2026)
Digital transformations in the academic domain demand a high level of readiness for digital instructional practice among pre-service teachers. Future educators’ advanced digital skills have a positive impact on the quality of the teaching process and learners’ academic outcomes. However, despite the high level of digital competence and positive attitude towards technology implementation, future teachers undergo constraints in the authentic setting to apply digital tools and platforms. The purpose of the paper is to identify pre-service teachers’ current preparation for digital instructional practice and make comparisons between self-reported and observed data. Quantitative research design was employed to answer the research questions; data collection tools included the survey and structured observation checklists. The research involved 97 third- and fourth-year students from the Kazakh National Women’s Teacher Training University. The differences between self-assessed and observational outcomes were measured through Spearman’s correlation. The findings reveal a moderate level of digital preparation and a considerable theory-practice gap. The theoretical value lies in creating a holistic comprehension of digital readiness. Practically, the results can empower university authorities to update the training curriculum focusing on the teaching components which were presented in the paper. Moreover, taking into consideration the significant gaps of the digital elements may be the basis of the innovative comprehensive framework. Key words: digital competence, digital readiness, pre-service teachers, digital instructional practice, pedagogical practice.